2023
DOI: 10.29333/ejmste/12809
|View full text |Cite
|
Sign up to set email alerts
|

Science learning in 3D virtual environment multi-users online in basic education stage

Abstract: Technological development is ever-evolving in all areas of life, its impact on the education field has emerged, and science is part of learning that teachers struggle with in their teaching methods. This study aimed to explore the effects of using a 3D virtual environment in learning science at the basic education stage and students’ attitudes towards their use. A quasi-experimental design was used in this study. A total of 99 students participated in the study, divided into two groups: an experimental group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Moreover, the use of 3D cancer spheroid models has received attention for their potential applications in drug-screening assessments, indicating their value in enhancing students' understanding of cancer cell behavior and drug delivery (Lee & Kim, 2021). These ndings align with the recommendation to use 3D virtual environments in science education, highlighting the broad applicability of 3D models in enhancing students' learning experiences (Shudayfat & Alsalhi, 2023).…”
Section: Introductionmentioning
confidence: 69%
“…Moreover, the use of 3D cancer spheroid models has received attention for their potential applications in drug-screening assessments, indicating their value in enhancing students' understanding of cancer cell behavior and drug delivery (Lee & Kim, 2021). These ndings align with the recommendation to use 3D virtual environments in science education, highlighting the broad applicability of 3D models in enhancing students' learning experiences (Shudayfat & Alsalhi, 2023).…”
Section: Introductionmentioning
confidence: 69%
“…The problem-based 3D virtual environments encourage students to learn by active participation, develop individual problem-solving skills, and share their ideas with peers (Phungsuk et al, 2017). Using a 3D virtual environment in science education has positive effects on student learning outcomes (Shudayfat & Alsalhi, 2023). Similar to our second conclusion, Aslan and Duruhan (2021) found that virtual learning environments designed based on the problem-based learning approach are more efficient in enhancing students' academic success and problem-solving skills compared to traditional methods in science lessons.…”
Section: Discussionmentioning
confidence: 99%
“…Within the context of IBL, Peffer et al (2015) and Shudayfat and Alsalhi (2023) found that the use of CSs in the classroom provided students with new opportunities to learn science in practice, permitting them to undertake investigative activities that are typically not doable in the classroom, along with equipping teachers and students' greater flexibility to perform scientifically realistic inquiries. Banda and Nzabahimana (2021) found that using PhET simulations effectively improves students' physics conceptual understanding.…”
Section: Computer Simulations and Inquiry-based Learningmentioning
confidence: 99%